DIPG-66. THE H3K27M MUTATION CAUSES WIDE-RANGING CHANGES MEDIATING DIPG TUMORIGENESIS - Lemma, Rakeb (Neuro Oncol, 2018)
BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is a nearly uniformly fatal pediatric brain tumor. 80% of DIPGs harbor a mutation (K27M) in genes encoding histones H3.1 or H3.3. We aimed to clarify the role of this mutation in tumorigenesis. METHODS: We transduced adult glioblastoma, pediatric glioblastoma, and DIPG cell lines (AM38, GBM1 and DIPG10 respectively) wild-type for H3.1 and H3.3 with a lentivirus-packaged H3K27M plasmid. We studied changes in the stably transduced cells compared to wild-type cells using western blot, a proliferation assay, a murine orthotopic xenograft model, RNA sequencing, karyotyping, and an inflammatory kinase assay. RESULTS: We observed a decrease in H3K27me3, an increase in H2AK119 ubiquitination and H3K27 acetylation, and an increase in proliferation rate, both in cell culture and an orthotopic xenograft model, in H3K27M relative to matched wild-type lines. Additionally, H3K27M cells exhibited a reduction in p16 or p53 protein expression, an increase in chromosomal abnormalities/fragmentation, and cytokine changes, including downregulation of the immune cell recruiter MCP-1, and upregulation of the proangiogenic factor VEGF. Geneset enrichment analysis showed H3K27M cell lines exhibited a more mesenchymal expression profile (GBM1: NES=4.84, FDR=0.0; DIPG10: NES=2.24, FDR=0.004), and greater expression of tumor invasiveness genes (GBM1: NES=5.52, FDR=0.0; DIPG10: NES=4.68, FDR=0.0), hallmark inflammatory response genes (NES=2.37, FDR=0.006; DIPG10: NES=3.49, FDR=0.0), and epithelial-to-mesenchymal transition genes (GBM1: NES=4.07, FDR=0.0; DIPG10: NES=4.06, FDR=0.0). CONCLUSIONS: The presence of H3K27M causes epigenetic, chromosomal, inflammatory, immunomodulatory, and gene expression changes that provide these cells a selective growth advantage over time. These findings raise several potential treatment strategies.